Prevalence of Hemoglobinopathies (β-Thalassemia and Sickle Cell Trait) in the Adult Population of Al Majma'ah, Saudi Arabia. (2nd January 2020) - Mir, Shabir A.; Alshehri, Bader M.; Alaidarous, Mohammed; Banawas, Saeed S.; Dukhyil, Abdul Aziz A. Bin; Alturki, Mohammad K.
Abstract: Despite the high prevalence of hemoglobinopathies in Saudi Arabia, the prevalence data in some regions are lacking. Updating the epidemiological survey of hemoglobinopathies at regular intervals is necessary to develop effective prevention and control strategies. Therefore, the primary aim of this study was to determine the prevalence of selected hemoglobinopathies in Saudi adults attending premarital screening at the King Khaled General Hospital (KKGH), Al Majma'ah, Saudi Arabia. The current retrospective study was approved by the Central Institutional Review Board (IRB) of the Ministry of Health (with central IRB log #2019-0039E) and was carried out at the above hospital. The data of the premarital couples, who attended the premarital screening center at KKGH from 1 October 2016 to 30 September 2019, was included in this study. A cation exchange high performance liquid chromatography (HPLC) system was used for screening of the selected hemoglobinopathies. In total, 3755 cases including 1953 (52.01%) males and 1802 (47.99%) females, were screened for hemoglobinopathies. Abnormal hemoglobin (Hb) fractions were observed in 38 (1.01%) cases. The prevalence of β-thalassemia (β-thal) trait was 0.69% (26/3755) and that of sickle cell trait 0.32% (12/3755). Our results showed that the prevalence of β-thal trait is higher than that of sickle cell trait in the adult population of Al Majma'ah. Further comprehensive programs should be carried out to determine the prevalence of hemoglobinopathies in various provinces and cities of Saudi Arabia and other countries. This will help to maintain the updated records of the disease incidence for improving the control measures.